Economic growth and its influence on the development of the Huánuco region - Pasquel Loarte, Lorenzo (2017)
The study, Economic Growth and its Influence on the Development of Huánuco Region, aims to determine the level of influence of economic growth in the development of the Huanuco region. Social policies strategically raised to achieve economic growth have a high level of influence on development. Investing more resources in education will enable greater economic growth by improving welfare and income distribution and increasing the potential growth capacity of society and therefore of the Huánuco Region. The implementation of the proposed alternatives to the use of resources in the health sector will be crucial to achieving economic growth as a result of the coordination of economists and doctors to achieve better communication aiming background raising the standard of health of the population of the Huánuco Region.  Exports as a source of economic growth have a high level of influence on employment, generating more jobs for residents. Social programs are properly applied to find a reasonable use of resources as key elements of economic growth for designing strategies for poverty alleviation in the Huanuco region.